2003
DOI: 10.1002/app.12526
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the molecular weight on the thermal and mechanical properties of ethylene/norbornene copolymers

Abstract: A series of ethylene-norbornene copolymers were synthesized using Me 2 Si(Me 4 Cp)(NtBu)TiCl 2 as the metallocene catalyst and methylaluminoxane (MAO) as the cocatalyst, with the same molecular characteristics except the molecular weight, to evaluate its influence on the determination of the glass transition temperature (T g ). The polymers were characterized using wide-angle X-ray scattering, differential scanning calorimetry, microhardness measurements, and dynamic mechanical thermal analysis. The value of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Ekizoglou et al [92] also studied the thermal properties of laboratory-made ENCs, having a norbornene molar fraction varying from 0.45 to 0.47. They showed that those ENCs had, respectively, T g varying from 108 to 123°C (from DSC measurements) or from 132 to 143°C (from DMTA measurements).…”
Section: Cyclic Olefin Copolymers (Coc) Development Of Cyclic Olefin mentioning
confidence: 97%
See 1 more Smart Citation
“…Ekizoglou et al [92] also studied the thermal properties of laboratory-made ENCs, having a norbornene molar fraction varying from 0.45 to 0.47. They showed that those ENCs had, respectively, T g varying from 108 to 123°C (from DSC measurements) or from 132 to 143°C (from DMTA measurements).…”
Section: Cyclic Olefin Copolymers (Coc) Development Of Cyclic Olefin mentioning
confidence: 97%
“…This type of ageing has been referenced by several authors [91][92][93][94][95][104][105][106]. Thermal ageing is performed to study the thermal stability and the thermal properties of materials.…”
Section: Ageing By Thermal Oxidationmentioning
confidence: 99%
“…Cyclic olefin copolymers (COCs) are a promising type of optical materials for their excellent performance in applications. The effects of copolymer composition, sequence distribution, and molecular weight on thermal properties of COC have been studied by many groups in the past decade 1–17. However, there are few reports on the relationships between chain microstructure and optical/surface properties.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of copolymer composition, sequence distribution, and molecular weight on thermal properties of COC have been studied by many groups in the past decade. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] However, there are few reports on the relationships between chain microstructure and optical/surface properties. Ou and Hsu 18 prepared COC/SiO 2 nanocomposites containing 1, 5, 10, and 15 wt % SiO 2 nanoparticles through solution blending and studied addition of SiO 2 on light transparency of composites.…”
Section: Introductionmentioning
confidence: 99%
“…30 The molecular weight of ENC (if not very high) also plays an important role in the thermal behaviors of the materials. 31 For the next generation optical applications, the ENC materials must have high NB content and uniformity in chain microstructure for higher T g and better transparency. To achieve this goal, both sequence length distribution and copolymer composition distribution (CCD) must be carefully designed and controlled.…”
mentioning
confidence: 99%